A new paradigm to understand and treat diabetic neuropathy - Hidmark, Asa S.; Fleming, Thomas; Mendler, Michael; Deshpande, Divija; Gröner, Jan; Müller, Beat P.; Pham, Mirko; Muckenthaler, Martina; Bendszus, Martin; Nawroth, Peter Paul (Experimental and clinical endocrinology & diabetes, 2014)
The clinical symptoms of diabetic neuropathy (DN) manifest in a time dependent manner as a positive symptoms (i. e. pain, hypersensitivity, tingling, cramps, cold feet etc.) during its early stages and by a loss of function (i. e. loss of sensory perception, delayed wound healing etc.) predominating in the later stages. Elevated blood glucose alone cannot explain the development and progression of DN and the lowering of blood glucose is insufficient in preventing and/or reversing neuropathy in patients with type 2 diabetes. Recently it has been shown that the endogenous reactive metabolite methylglyoxal (MG) can contribute to the gain of function via post-translational modification in DN of neuronal ion channels involved in chemosensing and action potential generation in nociceptive nerve endings. Dicarbonyls, such as MG, that are elevated in diabetic patients, modify DNA as well as extra- and intracellular proteins, leading to the formation of advanced glycation endproducts (AGEs). Increased formation of AGEs leads to increased cellular stress, dysfunction and ultimately cell death. The interaction of AGE-modified proteins through cell surface receptors, such as RAGE, can lead to increased cellular activation and sustained inflammatory responses, which are the molecular hallmarks of the later, degenerative, stages of DN. The direct and indirect effects of dicarbonyls on nerves or neuronal microvascular network provides a unifying mechanism for the development and progression of DN. Targeting the accumulation of MG and/or prevention of RAGE interactions may therefore provide new, more effective, therapeutic approaches for the treatment of DN.
Gesehen am 07.08.2020